2012
DOI: 10.1007/s11743-012-1359-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Surface Activities of Amidobetaine Surfactants with Ultra‐long Unsaturated Hydrophobic Chains

Abstract: Recent studies have shown that the surfactants bearing an ultra‐long hydrophobic chain (>C18) exhibit unique self‐assembly properties. However, their synthesis and surface activities have been less documented. In this work, monounsaturated alkyl dimethyl amidopropyl betaines, UCnDAB (n = 18, 22, and 24), were prepared by the reaction of the corresponding fatty acids with N,N‐dimethyl‐1,3‐propanediamine, followed by quaternization with sodium choloroacetate of the obtained intermediates. The intermediates and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 22 publications
0
45
0
Order By: Relevance
“…The CMC values of the newly synthesized cationic surfactant appear to be lower than other cationic surfactants based on dimethyl amino propyl amine (DMAPA) with the same carbon chain length and temperature [10,[19][20][21]. The CMC of the three prepared surfactants based on DMAPA is also lower than those of traditional cationic surfactants like alkylpyridinium bromides, alkyl trimethyl ammonium bromides, and alkyltripropylammonium bromides as shown in Table 2 [22][23][24][25][26].…”
Section: Surface Activitymentioning
confidence: 89%
“…The CMC values of the newly synthesized cationic surfactant appear to be lower than other cationic surfactants based on dimethyl amino propyl amine (DMAPA) with the same carbon chain length and temperature [10,[19][20][21]. The CMC of the three prepared surfactants based on DMAPA is also lower than those of traditional cationic surfactants like alkylpyridinium bromides, alkyl trimethyl ammonium bromides, and alkyltripropylammonium bromides as shown in Table 2 [22][23][24][25][26].…”
Section: Surface Activitymentioning
confidence: 89%
“…where R is the gas constant, T is the absolute temperature, N A is Avogadro's number and c is the concentration of surfactant in solution. For nonionic and zwitterionic surfactant, n = 1 [25][26][27][28]. The values of U max and A min , which are considered as a sign of packing densities of surfactant molecules at the air/liquid interface, are presented in Table 1.…”
Section: Effect Of Ph On the Aggregation Behavior Of Ddeaomentioning
confidence: 99%
“…Nevertheless, most investigations of amidobetaine surfactants so far have been limited to homologues with a chain length shorter than C18 due to the decreased water solubility when lengthening lipophilic tails, and the anionic head group is mainly confined to carboxylate [1]. Very recently, much attention has been shifted to ultra-longchain (C C18) amidobetaines [4-11, 13, 14] with diversified head groups including sulfobetaine [4, 9-11, 13, 14] and carboxylic betaine [5][6][7][8]. As expected, water solubility of these zwitterionic surfactants becomes poorer because of the increased chain length [9].…”
Section: Introductionmentioning
confidence: 99%
“…As expected, water solubility of these zwitterionic surfactants becomes poorer because of the increased chain length [9]. To make them useful practically, an external inorganic salt was always added [9,11] to decrease the Krafft temperature (T K ), or the monounsaturated C22 and C18 tails, i.e., erucyl or oleicyl, were used to replace the saturated behenyl and stearyl to offset the poor solubility, because the cis double bond located in the x-9 position results in a kink in the unsaturated hydrophobic tails, favoring a decrease in T K of the surfactants [5,8,11]. It was also found that these ultralong-chain amidobetaine surfactants are readily selfassembled into viscoelastic wormlike micelles (WLMs).…”
Section: Introductionmentioning
confidence: 99%